2021
DOI: 10.1680/jstbu.19.00135
|View full text |Cite
|
Sign up to set email alerts
|

A practical macro-mechanical model for the bend capacity of fibre-reinforced polymer bars

Abstract: DisclaimerThe AM is yet to be copyedited and formatted in journal house style but can still be read and referenced by quoting its unique reference number, the digital object identifier (DOI). Once the AM has been typeset, an 'uncorrected proof' PDF will replace the 'accepted manuscript' PDF. These formatted articles may still be corrected by the authors. During the Production process, errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal relate to these ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…It should be noted that Equations (1) to (4) are empirical and only depend on the geometry of the bend, whilst the bond characteristic between the FRP bar/concrete interface, type of FRP, and material composition are neglected. Recent research by Imjai et al [59] demonstrated that the predictions of Equations (1) to (4) do not match the experimental data available in the existing literature. As a result, Imjai et al proposed a new macromechanical-based equation (Equation (5a)) that more accurately calculates the bend capacity of a bent FRP reinforcement.…”
Section: References Remarksmentioning
confidence: 98%
See 4 more Smart Citations
“…It should be noted that Equations (1) to (4) are empirical and only depend on the geometry of the bend, whilst the bond characteristic between the FRP bar/concrete interface, type of FRP, and material composition are neglected. Recent research by Imjai et al [59] demonstrated that the predictions of Equations (1) to (4) do not match the experimental data available in the existing literature. As a result, Imjai et al proposed a new macromechanical-based equation (Equation (5a)) that more accurately calculates the bend capacity of a bent FRP reinforcement.…”
Section: References Remarksmentioning
confidence: 98%
“…Imjai et al [59] The model adopts the Tsai-Hill failure criterion for a unidirectional orthotropic laminar composite at a macroscopic level and considers force equilibrium at the bent zone. The model is calibrated using test results from 26 tests [33] and subsequently verified against 54 test results available in the literature.…”
Section: References Remarksmentioning
confidence: 99%
See 3 more Smart Citations